1997
DOI: 10.1097/00007890-199712270-00039
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus (Fk506) and Sirolimus (Rapamycin) in Combination Are Not Antagonistic but Produce Extended Graft Survival in Cardiac Transplantation in the Rat1,2

Abstract: Combined use of tacrolimus (FK506) with sirolimus (rapamycin [RAPA]) was examined in a model of vascularized heart allograft in the rat. For prevention of acute rejection, three different combinations of low doses of FK506 and RAPA from day 1 up to day 14 after transplantation produced significantly longer cardiac allograft survival than each agent alone (P<0.05). Identical results were observed in a model of reversal of ongoing acute rejection, where two combinations of low doses of FK506 and RAPA from day 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…By contrast, calcineurin inhibition using Tacro or inosine monophosphate dehydrogenase inhibition using MMF did not affect the fate of transplanted cells. The combination of immunosuppressive drugs required for preventing rejection of allogeneic hepatocytes in our studies was similar to that required previously in solid organ allografts, 21 despite the differences in immune responses elicited by solid organ or cell allografts. 22 Although most current immunosuppressive drugs do not specifically target cell subsets regulating the adoptive immune system, 23,24 we found that pharmacological regulation of the innate immune system benefited transplanted cell engraftment.…”
Section: Discussionsupporting
confidence: 77%
“…By contrast, calcineurin inhibition using Tacro or inosine monophosphate dehydrogenase inhibition using MMF did not affect the fate of transplanted cells. The combination of immunosuppressive drugs required for preventing rejection of allogeneic hepatocytes in our studies was similar to that required previously in solid organ allografts, 21 despite the differences in immune responses elicited by solid organ or cell allografts. 22 Although most current immunosuppressive drugs do not specifically target cell subsets regulating the adoptive immune system, 23,24 we found that pharmacological regulation of the innate immune system benefited transplanted cell engraftment.…”
Section: Discussionsupporting
confidence: 77%
“…The combination of sirolimus and tacrolimus is known to exhibit immunosuppressive synergy. 15 Numerous single-center reports describe sirolimus/tacrolimus-based immunosuppression in organ transplant recipients. [17][18][19][20][21][22][23][24][25] Consistent with the findings of our study, a retrospective analysis by El-Sabrout et al 19 emphasized the use of sirolimus loading doses to increase rejection-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Early preclinical experience, however, indicated that the sirolimus-tacrolimus combination exhibited immunosuppressive synergy. 15 Only a small fraction of the abundant FKBP-12 immunophilin needs to be occupied by these agents to achieve maximal immunosuppression. 16 There is an expanding body of literature on the successful clinical application of the combination of sirolimus-and tacrolimusbased immunosuppression in renal and nonerenal allograft recipients.…”
mentioning
confidence: 99%
“…Since similar FKBPs are required for successful CN inhibition by TRL and mTOR inhibition by SRL or EVL, pharmacological drug-drug interactions have been investigated by several groups. Dumont et al has shown that SRL and TRL are reciprocal antagonists [5,8], while others have demonstrated immunosuppressive synergism of these drugs [9,10].…”
Section: Introductionmentioning
confidence: 99%